Fit of probability distributions to monthly precipitation in the state of Pernambuco – Brazil (Research, Society and Development, 2020)
This study aimed to identify probability distribution that best fit monthly rainfall data for the state of Pernambuco - Brazil. The fits of six 2-parameters probability distributions were analyzed: gamma (GAM), log normal (LNORM), Weibull (WEI), Generalized Pareto (GP), Gumbel (GUM) and normal (NORM) for monthly rainfall data of 40 rainfall stations across the state of Pernambuco, from 1988 to 2017 (30 years). The Maximum Likelihood (ML) method was used to estimate the model parameters and the model selection was based on a modification of the Shapiro-Wilk statistic. The results showed the 2-parameters distributions are flexible enough to describe monthly precipitation data for the state of Pernambuco and the log normal, gamma, Weibull and GP models fitted better to the data. The Gumbel and normal models rarely adjusted to the data regardless of the month analyzed.